Rancang Bangun Sistem Informasi Penjualan dan Stok Air Galon Berbasis Website pada Usaha Depot Air Isi Ulang Cemani - Andreas Obrien Saragih; Marta Ardiyanto; Aprilisa Arum Sari (JURNAL ILMIAH SAINS TEKNOLOGI DAN INFORMASI, 2026)
This research aims to design and build a website-based information system for gallon water sales and stock at the Cemani Refill Water Depot. The current problem is that the sales and stock recording process is still done manually, resulting in frequent recording errors, delays in reporting, and difficulties in monitoring inventory. This condition results in less effective and efficient operational processes. The system development method used in this research is a prototype method, which includes requirements gathering, prototype creation, prototype evaluation, system development, system testing, system evaluation, and system use. The system design was carried out using Unified Modeling Language (UML), while system testing utilized Black Box Testing.The result of this research is a web-based information system capable of managing sales data, gallon water stock data, customer data, and generating reports quickly and accurately. Based on the results of testing using the Black Box Testing method, all system features, such as login, customer data management, stock management, sales transactions, and report generation, functioned as expected without error. This system is expected to improve work efficiency, minimize recording errors, and facilitate business owners in monitoring business progress in real time.